The Relationship of the Formation of Life Content and Creative Thinking of Military Servants (The Peerian Journal, 2023)
This article reveals the relationship between the meaning of life and the formation of creative thinking of military personnel. It shows the improvement of development by increasing the number of professionals who meet modern requirements and can be creative in every field. Important ideas about the formation of creative thinking among military personnel were put forward